Clinicopathological significance of cystatin A expression in progression of esophageal squamous cell carcinoma. Issue 15 (April 2018) - Shiba, Daiki; Terayama, Masayoshi; Yamada, Kazuhiko; Hagiwara, Teruki; Oyama, Chinatsu; Tamura-Nakano, Miwa; Igari, Toru; Yokoi, Chizu; Soma, Daisuke; Nohara, Kyoko; Yamashita, Satoshi; Dohi, Taeko; et al.
Abstract : Abstract: We previously conducted transcriptome analysis of a paired specimen of normal and esophageal squamous cell carcinoma (ESCC) tissues and found that mRNA expression of cystatin A (CSTA), a member of the cystatin superfamily, was perturbed in tumors compared with that in the background mucosa. However, little is known about the significance of CSTA expression in ESCC. The mRNA expression of CSTA was evaluated by qRT-PCR using 28 paired frozen samples of tumor and nontumor mucosae. The protein expression of CSTA was evaluated by the immunostaining of formalin-fixed, paraffin-embedded sections of ESCC samples from 59 patients who underwent surgery, and its relationship with clinical features was analyzed. The mRNA expression of CSTA was significantly decreased in ESCC compared with that in matched normal mucosa ( P < .0001). The protein expression of CSTA was limited in stratum granulosum and stratum spinosum but not in stratum basal in normal esophageal mucosa. It was reduced in all ESCC tissue samples compared with normal tissues; however, CSTA expression levels in tumors showed considerable variation. Of the 59 samples, 20 did not express CSTA, whereas 39 clearly expressed it. The expression of CSTA in tumors was significantly associated with pT classification (deeper tumor invasions) ( P = .0118) and advanced TNM stages ( P = .0497). In CSTA-positive tumor samples, CSTA-expressing cancer cells often expressed Ki67, a proliferation marker, which was in sharp contrast to normal mucosa, where Ki67-expressing cells were limited to the basal layer and did not express CSTA. Furthermore, CSTA expression was observed in all 22 lymph node metastases analyzed. Relatively high levels of CSTA expression in tumors were correlated with tumor progression and advanced cancer stage, including lymph node metastasis.